Risk Factors for Subsequential Carbapenem-Resistant Klebsiella pneumoniae Clinical Infection Among Rectal Carriers with Carbapenem-Resistant Klebsiella pneumoniae - Chen X; Liu Q; Liu W; Yan Q (Infection and Drug Resistance, 2020)
Xia Chen, Qingnuan Liu, Wen-en Liu, Qun Yan Department of Clinical Laboratory, Xiangya Hospital of Central South University, Changsha, Hunan, People’s Republic of ChinaCorrespondence: Qun Yan Tel +86-731-84327440Fax +86-731-84327332Email yanqun@csu.edu.cnPurpose: Carbapenem-resistant Klebsiella pneumoniae (CRKP) infection has become a critical clinical concern for its high mortality. Rectal carriage of CRKP has been reported playing an important role in CRKP infection; however, the extent to which carrier develops clinical CRKP infection is unclear. This study aimed to identify risk factors for developing subsequential CRKP clinical infection in rectal carriers with CRKP.Patients and Methods: Patients were screened for rectal carriage of CRKP in a tertiary university hospital; then, rectal CRKP carriers were divided into case group (those who developed subsequential clinical infection) and control group. Demographics, comorbid conditions, invasive procedures, antimicrobial exposure and other clinical parameters of those two groups were compared and analyzed using univariate and multivariate logistic regression analyses. Antimicrobial susceptibility profile and carbapenemase phenotype/genotype of those CRKP isolates were determined. MLST was applied to elucidate the molecular epidemiology of rectal CRKP isolates and clinical infection ones.Results: Eight hundred and thirty-five patients were screened for rectal CRKP carriage. A total of 62 CRKP rectal carriers were identified; among them, 37.1% (23/62) developed CRKP clinical infection. CRKP isolates were resistant to most of the tested antimicrobial agents. ST11 was the dominant MLST type in rectal CRKP isolates (71.0%), and all the 23 clinical infection isolates were ST11. Multivariate analysis revealed that admission to the intensive care unit (ICU) (OR, 6.753; P=0.006), being in coma condition (OR, 11.085; P=0.015) and receiving central venous catheter (OR, 8.628; P=0.003) were independent risk factors for progressing to subsequential CRKP infection among those rectal carriers.Conclusion: This study identified independent risk factors for developing subsequential CRKP clinical infection among CRKP rectal carriers, with being in coma condition as a new finding. It would help clinician target those high-risk rectal CRKP-colonized patients for prevention of subsequential clinical infection.Keywords: carbapenem-resistant Klebsiella pneumoniae, infection, risk factors, rectal carriage